Defining elite athletes: Issues in the study of expert performance in sport psychology - Swann, C.; Moran, A.; Piggott, D. (Psychology of Sport and Exercise, 2015)
Objectives: There has been considerable inconsistency and confusion in the definition of elite/expert athletes in sport psychology research, which has implications for studies conducted in this area and for the field as a whole. This study aimed to: (i) critically evaluate the ways in which recent research in sport psychology has defined elite/expert athletes; (ii) explore the rationale for using such athletes; and (iii) evaluate the conclusions that research in this field draws about the nature of expertise. Design: Conventional systematic review principles were employed to conduct a rigorous search and synthesise findings. Methods: A comprehensive literature search of SPORTDiscus, Academic Search Complete, PsycINFO, and PsycARTICLES was completed in September, 2013 which yielded 91 empirical studies published between 2010 and 2013. The primarily qualitative findings were analysed thematically. Results: Eight ways of defining elite/expert athletes were identified, ranging from Olympic champions to regional level competitors and those with as little as two years of experience in their sport. Three types of rationale were evident in these studies (i.e., "necessity", "exploratory" and "superior"); while findings also indicated that some elite athletes are psychologically idiosyncratic and perhaps even dysfunctional in their behaviour. Finally, only 19 of the 91 included studies provided conclusions about the nature of expertise in sport. Conclusions: This study suggests that the definitions of elite athletes vary on a continuum of validity, and the findings are translated into a taxonomy for classifying expert samples in sport psychology research in future. Recommendations are provided for researchers in this area.